Off-Season Swarming in the Japanese Honey Bee (Apis Cerana Japonica) - Morii, Kiyohito; Sakamoto, Yoshiko (Journal of Apicultural Science, 2024)
Several studies have reported fragmentary evidence that climate change is altering the phenology and behavior of honey bees. We compiled records of off-season swarming of the Japanese honey bee ( ) between autumn and winter to improve our understanding of the impact of climate change on the subspecies’ swarming phenology. Based on a survey of 311 beekeepers, eleven off-season swarming records were collected, with ten of them are from 2020 onward. The beekeepers who reported off-season swarming records had eight to twenty years of beekeeping experience, and they declared that they were witnessing off-season swarming for the first time, suggesting a recent increase. One possible factor contributing to the increase in off-season swarming is the temperature rise, as average autumn and winter temperatures in Japan have been increasing.